Floristic relationship between scrubland and grassland patches in the Mediterranean landscape of the Iberian Peninsula - Ramirez-Sanz, L; Casado, M A; Miguel, J M De (Plant Ecology, 2000)
In the rural Mediterranean landscape, mosaics of patches of sclerophyllous scrubland and semi-natural grasslands are frequent. The plant communities of these patches, which are physiognomically easy to recognise, are very heterogeneous. The objective of this paper is to determine whether the patches of scrub-grassland represent an integrated response unit of the vegetation with regard to the physical environment (climatic, geographical and edaphic factors) and human use, or whether, on the contrary, this is an independent response. In order to do this a total of 50 sampling sites where scrubland and grassland patches were in contact were studied along a 370 km E-W mesoclimatic gradient from central Spain to Portugal (Iberian Peninsula). Two distinct zones, the east and the west halves of the study area, were identiﬁed according to the plant communities. Within each of these zones, each type of patch responded to the previously mentioned factors, differentially and independently. This determined a general lack of inter-community association or ﬂoristic correlation between scrub and grassland plant communities in contact. The spatial association is a random process probably related to the particular human management realised on every scrubland and grassland patch. The scrub–grassland pattern, which is characteristic of the Mediterranean landscape, does not represent an integrated response unit of the vegetation to a given environment, but rather the sum of the independent responses to the environment of the two patches in contact.
Keywords: environmental gradient; inter-community association; mediterranean scrubland; rural landscape; spatial association; therophyte grasslands

Floristic relationship between scrubland and grassland patches in the Mediterranean landscape of the Iberian Peninsula - Ramirez-Sanz, L.; Casado, M. A.; Miguel, J. M. De (Plant Ecology, 2000)
In the rural Mediterranean landscape, mosaics of patches of sclerophyllous scrubland and semi-natural grasslands are frequent. The plant communities of these patches, which are physiognomically easy to recognise, are very heterogeneous. The objective of this paper is to determine whether the patches of scrub-grassland represent an integrated response unit of the vegetation with regard to the physical environment (climatic, geographical and edaphic factors) and human use, or whether, on the contrary, this is an independent response. In order to do this a total of 50 sampling sites where scrubland and grassland patches were in contact were studied along a 370 km E-W mesoclimatic gradient from central Spain to Portugal (Iberian Peninsula). Two distinct zones, the east and the west halves of the study area, were identiﬁed according to the plant communities. Within each of these zones, each type of patch responded to the previously mentioned factors, differentially and independently. This determined a general lack of inter-community association or ﬂoristic correlation between scrub and grassland plant communities in contact. The spatial association is a random process probably related to the particular human management realised on every scrubland and grassland patch. The scrub–grassland pattern, which is characteristic of the Mediterranean landscape, does not represent an integrated response unit of the vegetation to a given environment, but rather the sum of the independent responses to the environment of the two patches in contact.
Keywords: environmental gradient; inter-community association; mediterranean scrubland; rural landscape; spatial association; therophyte grasslands

Leaf morphology and leaf chemical composition in three Quercus (Fagaceae) species along a rainfall gradient in NE Spain - Castro-Diez, P (Trees-Structure and …, 1997)
mLeaf features were examined in three Quercus species (Q. coccifera, Q. ilex and Q. faginea) along a steep rainfall gradient in NE Spain. The analyzed leaf traits were area, thickness, density, specific mass, leaf concentration of nitrogen, phosphorous, lignin, cellulose and hemicellulose, both on a dry weight basis (Nw, Pw, Lw, Cw, Hw) and on an area basis (Na, Pa, La, Ca, Ha). These traits were regressed against annual precipitation and correlated with each other, revealing different response patterns in the three species. Q. faginea, a deciduous tree, did not show any significant correlation with rainfall. In Q. coccifera, an evergreen shrub, Nw, Na, Lw, La and Ca increased with higher annual rainfall, while Hw decreased. In Q. ilex, an evergreen tree, leaf area, Pw and Lw increased with precipitation, whereas specific leaf mass, thickness and Ha showed the reverse response. Correlations between the leaf features revealed that specific mass variation in Q. faginea and Q. coccifera could be explained by changes in leaf density, while in Q. ilex specific leaf mass was correlated with thickness. Specific leaf mass in the three species appeared positively correlated with all the chemical components on a leaf area basis except with lignin in Q. ilex and with P in Q. ilex and Q. faginea. In these two tree species Pw showed a negative correlation with specific leaf mass. It is suggested that each species has a different mechanism to cope with water shortage which is to a great extent related to its structure as a whole, and to its habit.
Keywords: environmental gradient; Leaf fibre content; leaf morphology; Leaf nutrient content; Mediterranean climate

Leaf morphology and leaf chemical composition in three Quercus (Fagaceae) species along a rainfall gradient in NE Spain - Castro-Díez, P. (Trees-Structure and …, 1997)
mLeaf features were examined in three Quercus species (Q. coccifera, Q. ilex and Q. faginea) along a steep rainfall gradient in NE Spain. The analyzed leaf traits were area, thickness, density, specific mass, leaf concentration of nitrogen, phosphorous, lignin, cellulose and hemicellulose, both on a dry weight basis (Nw, Pw, Lw, Cw, Hw) and on an area basis (Na, Pa, La, Ca, Ha). These traits were regressed against annual precipitation and correlated with each other, revealing different response patterns in the three species. Q. faginea, a deciduous tree, did not show any significant correlation with rainfall. In Q. coccifera, an evergreen shrub, Nw, Na, Lw, La and Ca increased with higher annual rainfall, while Hw decreased. In Q. ilex, an evergreen tree, leaf area, Pw and Lw increased with precipitation, whereas specific leaf mass, thickness and Ha showed the reverse response. Correlations between the leaf features revealed that specific mass variation in Q. faginea and Q. coccifera could be explained by changes in leaf density, while in Q. ilex specific leaf mass was correlated with thickness. Specific leaf mass in the three species appeared positively correlated with all the chemical components on a leaf area basis except with lignin in Q. ilex and with P in Q. ilex and Q. faginea. In these two tree species Pw showed a negative correlation with specific leaf mass. It is suggested that each species has a different mechanism to cope with water shortage which is to a great extent related to its structure as a whole, and to its habit.
Keywords: environmental gradient; Leaf fibre content; leaf morphology; Leaf nutrient content; Mediterranean climate